ANALISIS IMPLEMENTASI MMQ PADA BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH DITINJAU PADA ASPEK YURIDIS DAN FATWA SYARIAH - Faizin Rahmad Setiadi (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2020)
People's demand for housing continues to increase, while people's purchasing power is still low. The Islamic banking industry has a great opportunity to provide an alternative to sharia-based housing finance through Musyarakah Mutanaqisah (MMQ), namely joint financing based on ownership between the bank and the customer. This study tries to uncover the problems of implementing the MMQ contract from the legal and Islamic Shariah aspects. The analysis used in this study is descriptive analysis, namely the analysis carried out to evaluate the data or characteristics of reality. Keywords: housing finance, Musyarakah Mutanaqisah, product development